التكيف الدراسى وعلاقته بالكفاءة الذاتية العامة لدى طلبة كليتى العمارة وعلم النفس فى جامعة دمشق - حديفه، هبة بسام; جرمقاني، جمال (جامعة البعث, 2019)
The Aim of research is to study Academic adjustment and knowing its relationship to efficient self-General among the students of Damascus University, and reached 527 students, including 270 students and 257 students, and (287) specialization and scientific (240) Specialization literary; and application study researcher used a measure of self-efficacy General Gerozlm and Tchivirz, and the measure of Henry Borough Air academic, has revealed results for: a statistically significant relationship between adaptation academic and self-efficacy public, and the absence of differences in students 'grades on a scale of adaptation academic due to the variable sex, and the presence of differences in students' grades on a scale of self-efficacy due to the variable sex in favor of females, and the existence of differences in students 'grades on a scale of adaptation academic due to the variable specialization in favor of scientific specialization, and the existence of differences in students' grades on a scale of self-efficacy public due to the variable specialization in favor of scientific specialization.
هدف البحث دراسة التكيف الدراسي ومعرفة علاقته بالكفاءة الذاتية العامة لدى طلبة جامعة دمشق، على عينة بلغت (527) طالب وطالبه، منهم (270) طالبا و(257) طالبة، و(287) تخصص علمي و(240) تخصص أدبي؛ ولتطبيق الدراسة استخدمت الباحثة مقياس الكفاءة الذاتية العامة لجيروزلم وتشيفيرز، ومقياس هنري بورو للتكييف الدراسي، وقد كشفت نتائج البحث عن: وجود علاقة ذات دلالة إحصائية بين التكيف الدراسي والكفاءة الذاتية العامة، وعدم وجود فروق في درجات الطلاب على مقياس التكيف الأكاديمي تعزي لمتغير الجنس، ووجود فروق في درجات الطلاب على مقياس الكفاءة الذاتية تعزي لمتغير الجنس لصالح الإناث، ووجود فروق في درجات الطلاب على مقياس التكيف الدراسي تعزي لمتغير التخصص لصالح التخصص العلمي، ووجود فروق في درجات الطلاب على مقياس الكفاءة الذاتية العامة تعزى لمتغير التخصص لصالح التخصص العلمي.
Keywords: التكيف الدراسى -- الكفاءة الذاتية العامة -- طلبة الجامعات -- جامعة دمشق